Design of E-book Chapter on Impulse Momentum and Collision Materials Oriented CBR and Integrated 4C - Azzahra, Nabilah Iffah; Rahim, Fanny Rahmatina; Putra, Amali; Sari, Silvi Yulia (Journal of Innovative Physics Teaching, 2024)
As technology develops, developments in the education sector are also made to keep pace. One effort that can be made to develop education is to implement education that is integrated with 4C (Critical Thinking, Creative, Communication, and Collaboration) and using a case based reasoning (CBR) approach. Based on data found in the field, schools that have not implemented 4C in learning have learning outcomes that are still relatively low, so an e-book chapter was designed on integrated 4C CBR-oriented momentum and collision material for class X. This research aims to develop an electronic book 4C oriented which integrates CBR in physics subjects in class . This research was carried out using the ADDIE development model which consists of the Analysis, Design, Development and Evaluation stages. Each stage can be evaluated if necessary. The results of the study obtained data on the validity of the contents and constructs of the product by experts as well as the results of the practicality test in schools filled by physics subject teachers and class X students. The validation results carried out by the validator stated that the results of the e-book chapter product design were in the very category. So the product is valid.